Does it pay to study abroad? Evidence from Poland - Jacek Liwiński (Global Labor Organization (GLO), 2017)
Purpose: This paper tries to identify the impact of international student mobility on the first wages of tertiary education graduates in Poland. Design/methodology/approach: The author uses data from the nationwide tracer survey of Polish graduates (Graduate Tracer Study 2007) and regresses the hourly net wage rate in the first job after graduating from a higher education institution (HEI) on a rich set of individuals' characteristics. In order to reduce the bias due to selection to international student mobility the author includes a set of variables representing abilities and skills, characteristics of studies and international experience as control variables. The author addresses the possible selection to employment bias by using the Heckman correction with various exclusion restrictions. Findings: After controlling for observed heterogenity the author finds that Polish graduates who studied abroad for at least one month earn on average 18% more on their first job than those who studied in Poland only. However, the author also finds that this wage premium is partly explained by international economic migration after graduation. Studying abroad brings a wage premium only if it is followed by working abroad. Those who perform their first job in Poland do not obtain any wage premium from international student mobility. Originality/value: The main contribution of the paper is that it identifies international economic migration after graduation as another mechanism explaining why those, who studied abroad, earn more.
Keywords: I29; J24; J31; 330; international student mobility; wages; wage premium; Heckman correction